Correction: Anderson, H.B. et al. Using Ordinary Digital Cameras in Place of Near-Infrared Sensors to Derive Vegetation Indices for Phenology Studies of High Arctic Vegetation. Remote Sens. 2016, 8, 847 - Anderson, Helen; Nilsen, Lennart; Tømmervik, Hans; Karlsen, Stein Rune; Nagai, Shin; Cooper, Elisabeth J. (Remote Sensing, 2017)
Source at http://dx.doi.org/10.3390/rs9101003 After the publication of the research paper by Anderson et al. [ 1 ], a reanalysis of the data showed that mistakes had been introduced in the calculation of the greenness indices and the filtering for outliers prior to the statistical analysis. The calculation of the 2G_RBi and Channel G% indices were the most affected, while the filtering of the data for outliers had inadvertently removed too many data points which caused poor correlations. Unfortunately, these mistakes affect the conclusions of the paper. The original paper concluded that GRVI had a good correlation with NDVI in all vegetation types, and that 2G_RBi and Channel G% did not. After the reanalysis of the data, however, it became clear that all three vegetation indices show strong correlations with NDVI. In this correction, we present the corrected text and updated versions of Tables 1 and 2 and Figure 2.